The Impact of Religiosity on the Psychological Well-Being of Female Quran Memorizers at Pondok Pesantren Muntasyirul Ulum - Taufikurohman, Mohammad; Latipah, Eva (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The primary objectives of this research are to assess the religiosity of female students in the Quran memorization program at Pondok Pesantren Muntasyirul Ulum and to evaluate the improvement of their psychological well-being. This study seeks to fill the gap in existing literature by providing empirical evidence on how religious practices, specifically Quran memorization, influence the mental health of students in a pesantren setting. Utilizing a qualitative descriptive method, the research involved documentation, interviews, and observations with 31 selected female students. Data analysis was conducted through condensation, presentation, conclusion drawing, and verification, with data validity strengthened through triangulation of techniques and sources. The findings indicate that students exhibit high levels of religiosity across five key dimensions: belief, practice, knowledge, experience, and consequences. Additionally, significant improvements were noted in various aspects of psychological well-being, including self-acceptance, positive relations, autonomy, environmental mastery, purpose in life, and personal growth. This research underscores the integral role of a supportive religious environment in fostering both spiritual and psychological well-being, offering valuable insights for the development of educational practices that holistically address the needs of students. The study contributes to the broader understanding of how religious education can enhance mental health and provides a foundation for future research in similar educational contexts.